A vertebrate assemblage of Las Curtiembres Formation (Upper Cretaceous) of northwestern Argentina - Scanferla, Carlos Agustín (2011)
We describe an association of fossil vertebrates from the Morales Member of the Las Curtiembres Formation (Campanian) near Puente Morales, Salta Province, NW Argentina. The fossils include teleostean fishes, pipid frogs, pleurodiran turtles, mesoeucrocodylians, non-avian theropod dinosaurs, and enantiornithine birds. The vertebrate record is dominated by freshwater taxa. With the exception of pipid frogs, all taxa here described constitute new records for this sedimentary unit. Among them, the turtles are reported for the first time in the Cretaceous of northwestern Argentina (Salta Group). Additionally, the recently published small enantiornithine Intiornis inexpectatus enlarges the diversity of cretaceous birds from South America. Despite the fragmentary nature of the specimens, the information provided by this Late Cretaceous assemblage sheds new light on the composition of the continental vertebrate fauna in a paleontologically poorly known region of South America.